Synthesis, antituberculosis activity and molecular docking studies for novel naphthoquinone derivatives - W. Paengsri (2018)
A series of new substituted derivatives of 2-hydroxy-l, 4-naphthoquinone were successfully prepared by a Mannich reaction and evaluated for their in vitro anti-tuberculosis activity against Mycobacterium tuberculosis H37Ra. All the compounds were tested by Green Fluorescent Protein Microplate Assay (GFPMA) where rifampicin, streptomycin, isoniazid and ofloxacin were used as a reference drug. Two compounds, 2-hydroxy-3-((pyridin-2-ylamino)methyl)naphthalene-1,4-dione and 2-hydroxy-3-((2-hydroxyphenyl)(pyridin-2-ylamino)methyl) naphthalene-1,4-dione, exhibited a significant activity against tuberculosis. Three dimension structure of the most active compound, 2a with the enoyl ACP reductase from molecular docking in comparison with the crystallized inhibitor complex suggesting the potential use of novel substituted derivatives of 2-hydroxy-l,4-naphthoquinone as promising antituberculosis inhibitors. © 2012 Academic Journals Inc.